Phonetic and Epistemological Dimensions of the Letter Qāf (ق) in Surah Qāf: A Micro-Corpus Analysis through QSoft - Nugraha, Adhia; Marlina, Lina (STIQ Amuntai, 2025)
This study explores the phonetic miracle (iʿjāz shautī) of the Arabic letter Qāf (ق) in Surah Qāf, aiming to reveal its rhetorical, acoustic, and epistemological functions within Qur’anic discourse. Employing a descriptive qualitative method, the research applies micro-corpus analysis via the QSoft platform. Classical Arabic phonological theories—including makhārij al-ḥurūf, qalqalah, and tajānus ṣawtī—were systematically combined with semantic mapping of significant roots such as Q-R-A and Kh-L-Q to highlight the interplay between sound and meaning. The analysis identified 57 occurrences of the letter Qāf, with 76% situated in theological contexts directly related to themes of creation, resurrection, and divine power. Detailed assimilation patterns were observed: 20 progressive/regressive, 10 partial, and 27 unassimilated cases, all contributing to unique sound textures in the surah. Furthermore, the rhythmic recurrence of Qāf every 3–5 verses provides phonological anchoring, reinforcing the surah’s central messages while intensifying its spiritual resonance. This recurring sound pattern demonstrates that Qāf operates beyond its mere articulatory function, serving as a thematic and epistemological anchor that ensures continuity and coherence across the surah. Ultimately, the study concludes that iʿjāz shautī in Surah Qāf is not only an aesthetic phenomenon but also a measurable rhetorical force that strengthens Qur’anic daʿwah through phonetic precision, symbolic depth, and divine intentionality.